967 COVID READY Study: Cross-Sectional Survey of Medical Students Volunteering During the Coronavirus Pandemic (COVID-19) In the United Kingdom. (4th May 2021) - Byrne, M; Ashcroft, J; Wan, J; Alexander, L; Harvey, A; Schindler, N; Brassett, C
Abstract: Introduction: We aimed to identify the willingness, attitudes, and practice of medical students towards volunteering in a clinical capacity during the COVID-19 pandemic. Method: We distributed a cross-sectional survey from 2/5/2020 to 14/6/2020 to all medical students at UK medical schools. Results: A total of 1145 medical students from 36 medical schools completed the questionnaire. 82.7% of students were willing to volunteer, but only 34.3% had volunteered. The strongest predictors of willingness to volunteer on multiple linear regression were the beliefs that volunteering to work would benefit their medical education (estimate=0.35±0.03, adjusted P < 0.001) and that they would have a positive impact (estimate=0.33±0.03, adjusted P < 0.001). The majority of students were willing to take up a clinical role and were confident in having the necessary skills, but there was a discrepancy between the role's students were comfortable performing and those they were assigned. Thematic analysis of the issue's students would face when volunteering identified five themes: safety, professional practice, pressure to volunteer, finances and logistics, and education. Conclusions: This study identifies areas for consideration from those responsible for workforce planning, healthcare provision, and student safety. We provide recommendations to facilitate a volunteering process that is safer for students, staff, and patients.